Literature Review: Senam Kegel Terhadap Inkontinensia Urine Pada Lanjut Usia - nur isnaeni rahmah, dila (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2022)
Physiological changes include the nervous system, hearing, vision, cardiovascular, body temperature regulation, breathing, endocrine system, skin system, urinary tract system, musculoskeletal, and mental changes in the elderly, especially personality changes, and changes in memory. and intelligence, Lifestyle changes are psychosocial changes. Method using a literature study with a narrative method from research results published in 2018-2023. The search used the Kegel exercise keyword strategy at BAK frequency on Google Scholar and PubMed with the criteria used, namely articles that discuss incontinence and Kegel exercises which can be used as an alternative therapy for constipation, availability of full text, sample, year of publication in the last 5 years. From 10 articles it was described that Kegel exercises were proven to be effective as an alternative therapy for patients with constipation.